No evidence for a benefit from masker harmonicity in the perception of speech in noise - Steinmetzger, Kurt; Rosen, Stuart (The journal of the Acoustical Society of America, 2023)
When assessing the intelligibility of speech embedded in background noise, maskers with a harmonic spectral structure have been found to be much less detrimental to performance than noise-based interferers. While spectral “glimpsing” in between the resolved masker harmonics and reduced envelope modulations of harmonic maskers have been shown to contribute, this effect has primarily been attributed to the proposed ability of the auditory system to cancel harmonic maskers from the signal mixture. Here, speech intelligibility in the presence of harmonic and inharmonic maskers with similar spectral glimpsing opportunities and envelope modulation spectra was assessed to test the theory of harmonic cancellation. Speech reception thresholds obtained from normal-hearing listeners revealed no effect of masker harmonicity, neither for maskers with static nor dynamic pitch contours. The results show that harmonicity, or time-domain periodicity, as such, does not aid the segregation of speech and masker. Contrary to what might be assumed, this also implies that the saliency of the masker pitch did not affect auditory grouping. Instead, the current data suggest that the reduced masking effectiveness of harmonic sounds is due to the regular spacing of their spectral components.
Gesehen am 29.03.2023